Enhancing Traffic Efficiency of Unsignalized Intersections Through Signal Coordination: A Case Study of Pulchowk and Sahidchowk in Bharatpur - Acharya, Sandesh; Pokhrel, Asmita; Tiwari, Hemant (International Journal on Engineering Technology, 2025)
The aim of this study is to improve the traffic flow at Pulchowk and Sahidchowk intersections in Bharatpur, Nepal through signal coordination and two alternatives were adopted optimizing the cycle time and optimised signal timing with left-turn control. Traffic counts during peak hours and geometric data were measured, and intersection performance was evaluated on the basis of Level of Service (LOS), average delay, and Back of Queue (BOQ) length. Among the two alternatives analyzed, left turn control showed the highest improvement. The average delays during the morning peak hour were cut from 113.8 seconds to 54.2 seconds in Pulchowk and from 76.6 seconds to 35.6 seconds in Sahidchowk, while the back-of-queue lengths shortened from 821.5 meters to 414.5 meters and from 364.9 meters to 178.5 meters, respectively. During the peak evening times, delays decreased from 507.2 seconds to 62.4 seconds in Pulchowk and from 318.1 seconds to 32.7 seconds in Sahidchowk, with corresponding drops in BOQ from 1345.9 meters to 328.3 meters and from 861.3 meters to 277 meters, respectively. These findings showcase the efficiency of the integrated approach in averting delays and congestion in the study intersections.